Import Demand with Rational Expectations: Estimates for Bauxite, Cocoa, Coffee, and Petroleum - Husted, Steven; Kollintzas, Tryphon (The Review of Economics and Statistics, 1984)
Steven Husted, Tryphon Kollintzas, Import Demand with Rational Expectations: Estimates for Bauxite, Cocoa, Coffee, and Petroleum, The Review of Economics and Statistics, Vol. 66, No. 4 (Nov., 1984), pp. 608-618